2019
DOI: 10.1038/s41598-019-39385-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tropomyosin Receptor Kinase A Signaling Negatively Regulates Megakaryopoiesis and induces Thrombopoiesis

Abstract: Neurotrophin signaling modulates the differentiation and function of mature blood cells. The expression of neurotrophin receptors and ligands by hematopoietic and stromal cells of the bone marrow indicates that neurotrophins have the potential to regulate hematopoietic cell fate decisions. This study investigates the role of neurotrophins and Tropomyosin receptor kinases (Trk) in the development of megakaryocytes (MKs) and their progeny cells, platelets. Results indicate that primary human MKs and MK cells lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that the neurotrophin signaling pathway can regulate growth, differentiation, and apoptosis of neurons through p75 neurotrophin receptor and tyrosine kinase receptor [35; 36]. ErbB signaling pathway modulates neural development, cell proliferation, and differentitation and is also associated with neurodevelopment disorders [37]. The above-mentioned results suggest that the CV-B5 can lead to neurogenic diseases.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have reported that the neurotrophin signaling pathway can regulate growth, differentiation, and apoptosis of neurons through p75 neurotrophin receptor and tyrosine kinase receptor [35; 36]. ErbB signaling pathway modulates neural development, cell proliferation, and differentitation and is also associated with neurodevelopment disorders [37]. The above-mentioned results suggest that the CV-B5 can lead to neurogenic diseases.…”
Section: Discussionmentioning
confidence: 92%
“…Clustering of K562 scATAC-seq profiles using their low dimension projections in terms of match scores with reference cells revealed two major clusters (Figure 2c-d). For K562 cells belonging to the smaller cluster, some of the most frequently enriched genes, such as NTRK3 (TRKC) 14 and MAF have higher expression in megakaryocytes than erythrocytes (see cluster-1 in Figure 2c-d). MAF is known to cause differentiation of hematopoietic progenitor cells towards megakaryocytes and reduction of its transformation towards erythroid lineage 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have investigated the role of tropomyosin receptor kinase A (TrKA) in AML [43][44][45][46] . TrKA is a receptor tyrosine kinase normally responsible for the survival and differentiation of neuronal tissue 47 and is additionally implicated in early hematopoiesis 48,49 . TrKA gene fusions and overexpression may contribute to AML growth and survival 45 and although the presence of TrKA fusions sensitized hematopoietic malignancies to TrKA inhibitors 46 , the use of these kinase inhibitors as a single agent is not lethal in AML.…”
Section: Introductionmentioning
confidence: 99%